2018
DOI: 10.22540/jfsf-03-074
|View full text |Cite
|
Sign up to set email alerts
|

How do muscle and bone strengthening and balance activities (MBSBA) vary across the life course, and are there particular ages where MBSBA are most important?

Abstract: This narrative review focuses on the role of strength and balance activities throughout the lifecycle to improve physical capacity and reduce all-cause mortality. The evidence suggests strong associations in middle and older age, with poor balance, poor strength or poor physical function having strong associations with mortality. Currently in the UK, the proportions of adults (69% of men and 76% of women) not meeting the strength and balance guidelines (of 2 or more sessions/week) is concerning. This report id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 102 publications
0
25
0
1
Order By: Relevance
“…Thus, a higher physical capacity through physical exercise could potentially prolong the working life since workers with less physically demanding occupations retire later than workers with hard physical work [4]. Furthermore, an improved physical capacity will benefit the workers during the inherent age-related loss in muscle mass and strength with aging (sarcopenia) [49][50][51] and postpone the point when reaching the "disability threshold" where the workers are unable to meet their physical work demands [49,50]. Another initiative to reduce the pain intensity among eldercare workers, and thereby potentially prolong their working life, could be to adjust the work tasks to the worker's physical capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a higher physical capacity through physical exercise could potentially prolong the working life since workers with less physically demanding occupations retire later than workers with hard physical work [4]. Furthermore, an improved physical capacity will benefit the workers during the inherent age-related loss in muscle mass and strength with aging (sarcopenia) [49][50][51] and postpone the point when reaching the "disability threshold" where the workers are unable to meet their physical work demands [49,50]. Another initiative to reduce the pain intensity among eldercare workers, and thereby potentially prolong their working life, could be to adjust the work tasks to the worker's physical capacity.…”
Section: Discussionmentioning
confidence: 99%
“…The frequently falling women undertaking this FaME intervention significantly improved their strength, power and functional ability, all known risk factors for falls. These positive changes in muscle and physical function, along with significant reduction in falls rate 10 , may have had an important role in the reduced likelihood of a change in residence, hospitalization or death on follow up at 3 years, in these frequently falling older women 6,10 .…”
Section: Discussionmentioning
confidence: 99%
“…For a holistic approach to falls prevention in frailer older people, an intervention should not only reduce falls, but also improve strength, power, balance and functional ability if that person is below functionally important thresholds, so that they can remain as active and independent as possible 6,7 . Indeed, frequent fallers have poor outcomes, 27% of people who fell three or more times in a year were admitted to hospital, transferred to nursing homes or died at one year follow-up 8 .…”
Section: Introductionmentioning
confidence: 99%
“…With increased age, progressive dysfunctions on these systems would result in balance deficits. Where diversities in these functional disorders over age and cumulative impacts of these health inequities across life course would contribute to larger varieties in balance performance [ 23 , 24 ]. Previous study showed variability in gait velocity increased in older adults compared to young and middle-aged adults, which is in line with the present findings of increasing variations across ages [ 25 ].…”
Section: Discussionmentioning
confidence: 99%